ANALISIS PENGARUH MANFAAT WAKTU LUANG TERHADAP KEPUASAN WISATAWAN DI TAMAN WISATA ALAM ANGKE KAPUK JAKARTA UTARA - Halim, Patricia Lourensa; Nawangwulan, Wening Ramadhani Siti (Kepariwisataan: Jurnal Ilmiah, 2023)
This study describes the effect of the components of leisure benefit consisting of physical benefit, psychological benefit and social benefit on tourist satisfaction at Taman Wisata Alam Angke Kapuk, North Jakarta. This research uses explanative quantitative methods. The research population are tourists aged over 17 years old and have visited Taman Wisata Alam Angke Kapuk at least once from 2018 to 2022 with a sample of 400 respondents. Data analysis using statistic descriptive analysis method using IBM SPSS 25 software to test the established hypothesis. Through analysis and discussion, this study found that each component of leisure benefit (physical benefit, psychological benefit and social benefit) has a positive and significant effect on tourist satisfaction and leisure benefit have a positive and significant effect on tourist satisfaction by 75%.